Christian Ethics at the Boundary : Feminism and Theologies of Public Life - Guth, Karen V. (Book collections on Project MUSE., 2015)
In contemporary reflection on Christianity and politics, the work of realist, witness, and feminist theologians has been done in isolation--that is, each school has largely pursued its projects without incorporating the insights of the others. Christian Ethics at the Boundary offers the first approach to public and political theology developed at the boundaries that separate these approaches. Extending the strong contextual work of theologians like Robin W. Lovin and Stanley Hauerwas on one hand, and Kathryn Tanner, Monica A. Coleman, and Mary McClintock Fulkerson on the other, author Karen V. Guth engages the theologies of prominent public theologians Reinhold Niebuhr, John Howard Yoder, and Martin Luther King Jr. to identify new trajectories for future work in Christian ethics. By fostering constructive dialogue between these pivotal public theologians of the twentieth century, their contemporary representatives, and the vanguard voices in feminist and womanist theology, Guth identifies ecclesiology as a new agenda for realist theologians, feminism as a vital form of Christian politics for witness theologians, and "creative maladjustment" as a productive theological stance for all Christian ethicists. In doing so, the work displays an innovative method that enables a vivid, collaborative vision of Christian politics.